Shaping future perspectives in policy advice under deep, long-term uncertainty. The case of the Dutch Delta Committee. (March 2021) - Van 't Klooster, S.A.; Veenman, S.A.
Highlights: Focusing on (the interrelation between) government arrangements, the construction of long-term (un)certainty and the actual responses to long-term uncertainty, is conducive to understanding how future perspectives are shaped in policy advice under deep (long-term) uncertainty. This paper describes and analyses six different uncertainty responses used by the Dutch Delta Committee: embracing uncertainty, denying uncertainty, reducing uncertainty, delegating uncertainty, aligning uncertainty to the present and camouflaging uncertainty. A common and determinative response is reducing uncertainty and taking refuge in what is familiar (instead of embracing the 'unknown'). Formulating policy advice under deep uncertainty is a delicate balancing act between dealing with uncertainty and craving for certainty. Abstract: Since society is facing some major transformations, it is essential to understand how long-term perspectives in an uncertain context are shaped and the conditions and strategies used to enable their materialisation (Van Assche et al., this issue). This paper analyses how the future perspective of the Dutch Delta Committee amidst deep (longterm) uncertainty was shaped. It focusses on (the interrelation between) the government arrangement, the construction of long-term (un)certainty and the actual responses to long-term uncertainty while formulating future perspectives and a corresponding policy advice. The paper describes and analyses six different uncertainty responses that were used by the Dutch Delta Committee, i.e., embracing uncertainty, denying uncertainty, reducing uncertainty, delegating uncertainty, aligning uncertainty to the present and camouflaging uncertainty. We observed that the majority of the uncertainty responses were ways to guarantee progress in the face of uncertainty. Other responses were aimed towards creating a sense of urgency to act or towards postponing, delaying or even doing away with unwelcome decisions. A common and determinative response is reducing uncertainty and taking refuge in what is familiar. We conclude with the observation that formulating policy advice under deep uncertainty is a delicate balancing act between dealing with uncertainty and craving for certainty.